HANDHELD SPEED METERS IN POLAND AND THE STANDARD OF THE HUMAN RIGHTS OF THE DEFENCE - Skwarzyński, Michał (Review of European and Comparative Law, 2018)
This chapter describes the legal basics and the practice of using handheld radar and laser devices in speeding cases. The analysis concerns normative frameworks, unfortunately neglected, as well as indicates problems occurring in cases of offences related to speeding. In judicial practice, radar devices Iskra and lidar devices, colloquially called Ultralyte lasers, are most commonly used .Unfortunately, in judicial practice, the application of the normative framework for the use of lidar and radar equipment is subject to the principle in dubio pro radar.